Allene‐Based Gold‐Catalyzed Stereodivergent Synthesis of Azapolycyclic Derivatives of Unusual Structure. Issue 9 (27th April 2016) - Alcaide, Benito; Almendros, Pedro; Martín‐Montero, Raúl; Ruiz, M. Pilar
Abstract: The present study provides insights into the manner in which the configuration of β‐aminoallene precursors affects their gold‐catalyzed cyclization reactions. The reactivity can be switched by using indolizidinone‐tethered β‐aminoallenes bearing the syn ‐ or the anti ‐disposition of both protons at the α‐ and β‐allenic stereocenters. Fused heterocycles (seven examples, 60–75% yields) are obtained from the syn ‐precursors, while a dimerization–aminoketalization–spirocyclization sequence to afford benzo[ b ]pyrrolo[3, 2, 1‐ ij ][1, 7]naphthyridin‐1‐ones (four examples, 34–48% yields) can be achieved starting from their anti ‐isomers. Abstract :